Peperites: Insight into the Submarine Eruptions within Walash Volcanosedimentary Group, Mawat Area, Iraqi Kurdistan Region - Qaradaghi, Jabbar M. A.; Merza, Tola A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
Peperites are volcanosedimentary materials generated by the mingling of magma and unconsolidated wet sediments. They have unique insights into submarine volcanisms and the tectonic environments where they form. For the 1st time, the authors identified two types of peperites (blocky and fluidal) hosted by micritic limestone rocks in the Walash Volcanosedimentary Group of the Mawat area, Kurdistan Region-Iraq. They are designated as peperitic facies one and two (PF1 and PF2) and consist of black basaltic rocks mixed with chocolate-brown micritic limestone rocks. Their abundance demonstrates the contemporaneity of deep marine sediment deposition and submarine volcanism during Walash’s nascent arc. Despite hydrothermal alteration, the basaltic rocks retained their magmatic textures. Basaltic rocks comprise mainly albite, anorthite, diopside, hematite, and alkali-feldspar. Calcite dominates micritic limestone rocks, while quartz is minor. Based on geochemical data, igneous sections are basaltic rocks with tholeiitic series that are strongly enriched in Light Rare Earth Elements with low concentration ratios of (La/Yb) and (Sr/Y), indicating geochemical affinity to normal island arc basalt with a primitive arc signature. Furthermore, their formation is thought to be caused by partial melting of subducted slabs deep within 30 km and the associated derived fluids above the subducted slab. Thirteen species of planktonic foraminifera (Morozovella) are identified through paleontological research and biostratigraphy. Using these various tools lead the authors to illustrate the tectonic setting of the formation of peperitic rocks in arc fronts of the subducted Walash arc during the Middle to Late Paleocene (60 Ma).